Desain Indutri Sebagai Karya Yang Dilindungi (HAKI) - AR, Azhari; Rahmadani, Gema (Universitas Islam Sumatera Utara, 2019)
A designer has a copyright on the results of his creativity in the form of a blueprint and has the exclusive right to make the artwork into three or two dimensions. The industrial design law is directed at protecting mass-produced goods. People prefer protection with the right to industrial design, which is only protected for 10 years. This is because a design is very easy and can be imitated quickly by the general public. When it is protected by copyright, it becomes ineffective and wasteful. Copyright does not protect mass products.Keywords: Design, Industry, Work, Intellectual Property Rights